Identification of BRCA1:c.5470_5477del as a Founder Mutation in Chinese Ovarian Cancer Patients - Li, Jun; Han, Sile; Zhang, Cuiyun; Luo, Yanlin; Wang, Li; Wang, Ping; Wang, Yi; Xia, Qingxin; Wang, Xiaoyan; Wei, Bing; Ma, Jie; Li, Hongle; et al. (Frontiers in Oncology, 2021)
Predisposition of germline BRCA1/2 mutations (gBRCAMUT) increases the risk of breast and ovarian cancer in females, but the mutation prevalence and spectrum are highly ethnicity-specific with different recurrent mutations being reported in different populations. Hereby, we performed hybridization-based target sequencing of BRCA1/2 in 530 ovarian cancer patients from Henan, the central region of China, followed by haplotype analysis of 6 short tandem repeat (STR) markers in the patients with recurrent mutations to determine their founder effect. About 28.3% (150/530) of the OC patients in our cohort harbored gBRCAMUT; of the 151 mutations, 117 in BRCA1 and 34 in BRCA2, identified in this study, BRCA1:c.5470_5477del, c.981_982del and c.4065_4068del are the top3 mutants, recurrently detected in 8, 7, and 6 independent patients respectively. Haplotype analysis identified a region of 0.6MB genomic length covering BRCA1 highly conserved across all 8 carriers of BRCA1:c.5470_5477del, but not c.981_982del, suggesting a consequence of founder effect. Retrospective analysis in a subgroup of serous ovarian cancer patients revealed gBRCAMUT status was not associated the progression-free survival (PFS); instead, an expression of Ki-67% ≥50% was associated with a shorter PFS (p=0.041). In conclusion, patients with pathogenic or likely pathogenic gBRCAMUT account for 28.3% of the OC cases from Henan, and BRCA1:c.5470_5477del, the most frequently detected mutation in Henan patients, is a founder mutation in the population.